Effect of Climate Change on Livestock Production in Somalia - Ahmed, Mumin Rage; Sabrie, Hassan Omar; Rage, Guuleed Abdullahi (FUDMA Journal of Sciences, 2026)
This paper employs how climate change influences animal production in Somalia. using Time series data obtained from WDI and WB in 1990-2020. the study applied ARDL Model and the analysis was done in E-Views-12 Software. Distinct variables were used such as Annual temperature, Carbon dioxide, rural population. Carbon dioxide has positive significant effect in livestock production but Annual temperature and rural population have negative significant effect in the livestock production. All data variables were tested by the unit root livestock production, CO2 and rural population were stationary at first difference but non- stationary at level. the study found that one-unit increase in annual temperature raised livestock production by 32.5% and it is significant level at 5%. Also, one-unit increase in CO2 caused to increase livestock production by 0.006 a level that is not significant. Finally, one-unit increase of rural population will result to decrease livestock production by -1.37% and it is statistically not significant but in short run period all variables are significant. This paper concludes that in long term, annual temperature and CO2 likely lead to increased livestock production and loss by Rural population. The study recommends to improve the service of veterinarians in order to prevent animal illness related to climate, which lowers productivity and increases mortality in animal production.